Slovenian Pulse 4/2012 - Makarovič, Matej; Rončević, Borut; Tomšič, Matevž; Besednjak Valič, Tamara (Arhiv druzboslovnih podatkov, 2011)
V okviru sklopa vprašanj o blaginji v Sloveniji se ugotavlja, kako prebivalci Slovenije doživljajo današnje gospodarske razmere: kako vidijo svoj materialni standard, kako živijo sami in kako se v Sloveniji na splošno živi, smo napredovali ali nazadovali in kaj naj bi prinesla prihodnost. Ugotavlja se tudi, kolikšne so danes socialne neenakosti med ljudmi in kolikšen je strah pred izgubo zaposlitve. V sklopu aktualno političnih vprašanj se preverja podpora vladi in strankarske preference, stališče o varčevalnih ukrepih in predlaganem začasnem znižanju plač javnih uslužbencev ter stavki sindikatov. The study focuses on perception of person's own material conditions and satisfaction with it relatively to evaluation of material conditions of Slovenia in general, assessment of Slovenian society class structure on the basis of self-classification in social classes. Perception of economic crisis with its fears and suspense can be analysed related to the distribution of economic crisis perception in the social structure framework, to political party preferences and to some other topical questions. The study focuses on perception of person's own material conditions and satisfaction with it relatively to evaluation of material conditions of Slovenia in general, assessment of Slovenian society class structure on the basis of self-classification in social classes. Perception of economic crisis with its fears and suspense can be analysed related to the distribution of economic crisis perception in the social structure framework, to political party preferences and to some other topical questions. The study focuses on perception of person's own material conditions and satisfaction with it relatively to evaluation of material conditions of Slovenia in general, assessment of Slovenian society class structure on the basis of self-classification in social classes. Perception of economic crisis with its fears and suspense can be analysed related to the distribution of economic crisis perception in the social structure ...